Супербой, Маньяк и Робот: [повесть : для среднего школьного возраста] / Эдуард Веркин - Веркин Эдуард Николаевич (Настоящие приключения, 2016)
Экземпляры: (20160428) / Инвентарный номер: 39224 / Цена: 181.00; 208.00 / Авт.знак: В 32 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6